Proposals for a National Health Service - Great Britain. National Health Service
1946-01 1946 1940s 16 pages Other Services. Eye Service. 44. The objective will be the provision of special clinics, as part of the hospital service, at which all will be entitled to eye-testing and the supply of spectacles either from the clinic or on a prescription given at the clinic and taken to a dispensing optician. These clinics will be staffed by ophthalmologists (i.e. full eye specialists on hospital staffs) and refractionists (i.e. sight-testing opticians). The ophthalmologists will be responsible for the clinics, but the extent to which they delegate eye-testing to refractionists will be a matter of internal arrangement. These clinics will be developed as widely and rapidly as possible, but temporary supplementary arrangements making use of existing sight-testing facilities may be required. Public Health Laboratories. 45. A public health pathological laboratory service for the control of infectious diseases will be provided on a national basis by the Minister of Health, in the first instance through the agency of the Medical Research Council. The powers of local authorities to provide laboratories will continue. Blood Transfusion. 46. The Minister will be empowered to make national arrangements for obtaining supplies of human blood, for making these available for transfusion and for preparing and supplying blood products. 292/847/4/83